Pola Penerapan STEAM dalam Produksi Playmat Interaktif untuk Pendidikan Muatan Lokal di Sekolah Pinggiran Kabupaten Pacitan - Prasetyo, Abdul Rahman; Wulandari, Dwi; Ratnawati, Ike; Rahmawati, Nila; Aruna, Alby; Marcelliantika, Adinda; Surya, Eka Putri (IAI Nasional Laa Roiba Bogor, 2024)
The implementation pattern of this community service aims to understand how to implement the STEAM method (Science, Technology, Engineering, Arts, Mathematics) in the production of interactive playmats intended to enhance local content education in schools on the outskirts of Pacitan Regency. Through a participatory approach, this activity involves teachers and students in the design and production process of playmats, which are designed to facilitate interactive and enjoyable learning. The results of the implementation show that the application of the STEAM method not only enhances students' creativity and technical skills but also strengthens their understanding of local culture. The evaluation of playmat usage indicates a significant increase in students' interest and engagement in learning. Therefore, this activity recommends that integrating the STEAM method into local educational products can be an effective model for developing education in remote areas.